Active multiple tuned mass dampers for structures under the ground acceleration. - Li, Chunxiang (Earthquake engineering & structural dynamics.)
Active multiple tuned mass dampers (AMTMD) consisting of many active tuned mass dampers (ATMDs) with a uniform distribution of natural frequencies have been, for the first time, proposed for attenuating undesirable vibrations of a structure under the ground acceleration. The multiple tuned mass dampers (MTMD) in the AMTMD is manufactured by keeping the stiffness and damping constant and varying the mass. The control forces in the AMTMD are generated through keeping the identical displacement and velocity feedback gain and varying the acceleration feedback gain. The structure is represented by its mode generalized system in the specific vibration mode being controlled using the mode reduced order method. The optimum parameters of the AMTMD are investigated to delineate the influence of the important parameters on the effectiveness and robustness of the AMTMD by conducting a numerical searching technique. The parameters include the frequency spacing, average damping ratio, tuning frequency ratio, total number and normalized acceleration feedback gain coefficient. The criterion, which can be stated as the minimization of the minimum values of the maximum dynamic magnification factors (i.e. Min.Min. Max. DMF), is chosen for the optimum searching. Additionally, for the sake of comparison, the results of the optimum MTMD (the passive couterpart of AMTMD) and ATMD are also taken into account in the present paper. It is demonstrated that the proposed AMTMD can be expected to significantly reduce the oscillations of structures under the ground acceleration. It is also shown that the AMTMD can remarkably improve the performance of the MTMD and has higher effectiveness than ATMD.